Anatomical knowledge gain through a clay‐modeling exercise compared to live and video observations. Issue 6 (12th March 2014) - Kooloos, Jan G.M.; Schepens‐Franke, Annelieke N.; Bergman, Esther M.; Donders, Rogier A.R.T.; Vorstenbosch, Marc A.T.M.
<x xml:space="preserve">Abstract</x> Clay modeling is increasingly used as a teaching method other than dissection. The haptic experience during clay modeling is supposed to correspond to the learning effect of manipulations during exercises in the dissection room involving tissues and organs. We questioned this assumption in two pretest–post‐test experiments. In these experiments, the learning effects of clay modeling were compared to either live observations (Experiment I) or video observations (Experiment II) of the clay‐modeling exercise. The effects of learning were measured with multiple choice questions, extended matching questions, and recognition of structures on illustrations of cross‐sections. Analysis of covariance with pretest scores as the covariate was used to elaborate the results. Experiment I showed a significantly higher post‐test score for the observers, whereas Experiment II showed a significantly higher post‐test score for the clay modelers. This study shows that (1) students who perform clay‐modeling exercises show less gain in anatomical knowledge than students who attentively observe the same exercise being carried out and (2) performing a clay‐modeling exercise is better in anatomical knowledge gain compared to the study of a video of the recorded exercise. The most important learning effect seems to be the engagement in the exercise, focusing attention and stimulating time on task. Anat Sci Educ 7: 420–429. © 2014 American Association of Anatomists.